Asymptomatic Venous Thromboembolic Disease in a patient with Down syndrome: A case report and clinical presentation - De-La-Cruz-Chuquilin, Enrique (2021)
Introduction: Vascular disorders are frequent in Down Syndrome (SD); however, it is unclear whether such patients are at increased risk for venous thromboembolic events, making this association rare. Clinical case: We report the case of a 27-year-old female patient with DS who presented a large central embolus in the pulmonary artery and its middle lobular branch on the right side; likewise, a thrombus in the femoral artery that almost completely blocked its diameter, whose presentation is asymptomatic; being diagnosed by CT Angiography and Doppler ultrasound accordingly. Enoxaparin and Warfarin were given as treatment, having a favorable evolution. Conclusion: Much attention should be paid to the correlation between venous thromboembolic disease and Down syndrome, and a wide effort should be made in its prevention, detection and treatment.